Oxidação de CO sobre nanoestruturas controladas e de interiores vazios de AgPt dispersas em óxidos - Silva, Alisson Henrique Marques da (2016)
The CO oxidation is considered one of the most studied reactions in heterogeneous catalysis. Although several studies have been developed in this field, the impact of some properties of catalysts, such as the oxygen mobility, the number of active sites and the preferential exposure of surface facets, on their catalytic performance remains unclear. To progress in the understanding of this area, in the present study nanostructures with controlled size, geometry and morphology dispersed in oxides were applied to investigate two independent effects on the CO oxidation: (i) the effect of the nature of oxides (SiO2, TiO2, CeO2 and Al2O3) as support for AgPt nanoshells displaying rough surfaces (NCR); and (ii) the effect of the morphology of AgPt nanoshells displaying smooth (NCL) or rough (NCR) surfaces, and nanotubes displaying smooth (NTL) or rough (NTR) surfaces. More specifically, was investigated (i) how the mobility of the structural oxygen affects the catalytic performance; and (ii) how the number of Pt active sites and the nature of exposed surface facets influence the CO oxidation on nanostructures displaying controlled surface morphology (smooth or rough surfaces), shape (spherical or one-dimensional), size, and chemical composition. In the first study, the catalytic performance decreased in the following order: NCR/CeO2 > NCR/TiO2 > NCR/Al2O3 ≈ NCR/SiO2. The formation of oxygen vacancies, the reducibility of the oxides and the oxygen storage capacity (OSC) were investigated by Raman spectroscopy, temperature-programmed reduction and OSC technique, respectively. The catalytic performances were related with the mobility of the structural oxygen. The result observed for the NCR/TiO2 catalyst was associated with the presence of oxidized species, which are capable to perform the redox process, after the deposition of NCR on the TiO2. These species were not observed for the NCR/Al2O3 and NCR/SiO2 catalysts. In this study, the best result observed for the NCR/CeO2 catalyst was associated with the strong metal-support interaction between NCR and CeO2, resulting in the most pronounced structural oxygen mobility for the NCR/CeO2 catalyst in comparison with the other materials. These results attest the strong dependence of the catalytic performance on the mobility of the structural oxygen, which is promoted by metal-support interactions. In the second study, the catalytic performance decreased in the following order: NTL/SiO2 > NTR/SiO2 ≈ NCL/SiO2 > NCR/SiO2. The better catalytic activity observed with the NCL/SiO2 relative to that of the NCR/SiO2 was associated with its higher number of Pt active sites (~ 3 times higher). The better result observed with the NTL/SiO2 relative to that of the NTR/SiO2 was related with the preferential exposure of {100} facets, which are more active towards the CO oxidation than {111} and {110} facets. Interestingly, the NTL/SiO2 also displayed higher catalytic activity when compared to that of the NCL/SiO2, which presents similar amount of Pt surface atoms. This result indicates that the preferential exposure of {100} facets can be more effective with respect to the number of active sites. In this way, in Pt-based materials, the preferential exposure of {100} facets may play a significant role in the optimization of the catalytic performance for CO oxidation.